Character Development of Students in Public High School 4 Surabaya Through The Role of School Culture and Parenting Style - Dena, Suhaidin; Darmawan, Didit (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to explore the influence of school culture and parenting on students' character building at SMA Negeri 4 Surabaya. School culture, based on ethical and moral values as the main pillars, creates a supportive environment for students' character development. Parenting, which includes attention, emotional support, and open communication, is identified as a crucial factor to shape students' character. The two independent variables determining student character will be the focus of this study. With a quantitative approach using the regression analysis method, this study proves that school culture and parenting significantly contribute to students' character formation. The findings of this study provide a strong theoretical basis and have practical implications for educational policy development. This study provides guidance for schools and parents to design educational strategies to support students' positive development. The conclusions of this study provide a foundation for the implementation of educational policies that support students' character at SMA Negeri 4 Surabaya.